A Convenient One-Pot Process for Converting Thiols into Sulfonyl Fluorides Using H2O2 as an Oxidant - Tao, Guang; Fayad, Eman; Abu Ali, Ola A.; Oyom, Bright; Qin, Hua-Li (Synthesis, 2024)
A novel protocol for synthesizing sulfonyl fluorides from thiols in one pot is reported. Utilizing SOCl2 and H2O2 as low-cost and convenient reagents allows the direct oxidative chlorination of readily available thiol derivatives to give the corresponding sulfonyl chlorides, with subsequent fluoride–chloride exchange mediated by KHF2 giving access to the desired sulfonyl fluorides. This transformation features mild conditions, operational simplicity and high efficiency, and utilizes a broad substrate scope, including a variety of aryl, alkyl, benzyl and heteroaryl thiols.
Keywords: thiols; sulfonyl fluorides; hydrogen peroxide; one-pot process; oxidative chlorination